EU Migration to and from the UK After Brexit - Carlos Vargas-Silva (Intereconomics, 2016)
In the 2016 referendum over the UK's membership of the EU, the question of how Brexit would impact migration to the UK was a major point of contention. Those leading the campaign to leave the EU promised lower levels of immigration and the introduction of an “Australian type points based system” to regulate future inflows of EU nationals to the country, while at the same time maintaining access to the EU single market. At the same time, the status of EU nationals already living in the UK was not a key topic in the debate. The leaders of the campaign to leave the EU suggested that EU nationals already residing in the UK would be granted some form of residence permit and would retain most of their current rights. Likewise, there was little concern about the legal status of UK nationals in other EU countries and the argument that the “EU would be obliged to grant permanent settlement rights to Britons living in Ireland and mainland Europe”.
Keywords: 330